# Surds

posted by .

Solve in the exact form.

(sqrt of 4x+1)+(sqrt of x+1)=2

Someone showed me to do this next:
Square both sides..so..
4x+1+2((sqrt of 4x+1)•(sqrt of x+1))=4
I do not understand where the 2 come from ..and why do we need to multiply the sqrt of 4x+1 and sqrt of x+1 together to get the product.......??????????

• Surds -

Whoops I meant ..
Sqrt of x+3, not x+1..

• Surds -

(a+b)^2 = a^2 + ab + b^2

• Surds -

a+b)^2 = a^2 + 2ab + b^2
(sqrt of 4x+1)+(sqrt of x+3)=2
4x+1 + 2 (sqrt (x+3)sqrt(4x+1)) + x+3=4
5x+4 +2 (sqrt (5x+4)=4
5x+2sqrt(5x+4)=0
5x=-2(sqrt(5x+4)
square both sides
25x^2=4(5x+3)
25x^2-20x-12=0
(5x+2)(5x-6)=0

x=-12/5 or x=6/5

check that.

• Surds -

Hmmm. I get

√(4x+1)+√(x+3)=2
4x+1 + 2√(4x^2+13x+3) + x+3 = 4
5x = -2√(4x^2+13x+3)
25x^2 = 4(4x^2+13x+3)
25x^2 = 16x^2 + 52x + 12
9x^2 - 52x - 12 = 0
(9x+2)(x-6) = 0
x = -2/9 , 6

But x=6 does not satisfy the original equation, so -2/9 is the only solution.

## Similar Questions

1. ### MATH

I need to simply this equation, but I got stuck. h/(4-sqrt(16+h)) = y First, I multiplied (4+sqrt(16+h)/(4+sqrt(16+h) to both sides, and I ended up with h(4+sqrt(16+h)/-h. Is this correct?
2. ### Algebra

Solve for s: h=(square root of 3)times s/2 and solve for h V= (pi)r squared h / 3 Solve for s: h=(square root of 3)times s/2 Multiply both sides by 2. 2h = (sqrt 3)*s*2/2 which cancels the 2 on the right. 2h = (sqrt 3)*s Now divide …

l = lim as x approaches 0 of x/(the square root of (1+x) - the square root of (1-x) decide whether: l=-1 or l=0 or l=1 Let me make sure I understand the question. Do we have lim x->0 x/[sqrt(1+x) - sqrt(1-x)] ?
4. ### math

determine the area of triangle abc when side ab= square root of x, side bc= square root of x, and side ca= the square root of the square root of x. So how do I solve it. How do I add the square root of x + the square root of x + the …
5. ### Inequality

When I solve the inquality 2x^2 - 6 < 0, I get x < + or - sqrt(3) So how do I write the solution?

7. ### math

solve 2x^2+3x+8=0 and express the solutions in a+bi form. Let's use the quadratic formula to solve for x and express those solutions in a+bi form. x = [-b + or - sqrt(b^2 - 4ac)]/2a Note: sqrt = square root. a = 2, b = 3, and c = 8 …
8. ### math,algebra,help

Directions are simplify by combining like terms. x radiacal 18 -3 radical 8x^2 can someone show me how to do these types of problems. thanks I cant determine the second term. For the first, I think you meant x sqrt(18) which reduces …
9. ### Math

How do you find a square root of a number that's not a perfect square?